2023
DOI: 10.1111/hex.13706
|View full text |Cite
|
Sign up to set email alerts
|

Provision of and trust in COVID‐19 vaccines information: Perspectives of people who have had COVID‐19

Abstract: Aim:The aim of this study was to understand the provision and need, quality of and trust in COVID-19 vaccines information from the perspectives of people who have had COVID-19 infection.Method: People who have had a COVID-19 infection were approached via their general practice and invited to participate in the Nivel Corona Cohort. They completed questionnaires at baseline (Q1), and at three months (Q2). Outcome measures were based on health information-seeking behaviour, as used in the Comprehensive Model of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…We found that HCWs who had never been tested for the coronavirus were less likely to take the vaccines than were the participants who had ever been tested. A study by Laura et al (2023) reported that 96% of participants consumed a COVID-19 vaccine at least once, mostly after infection with the coronavirus (37). This difference in uptake could be due to differences in risk perceptions among HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…We found that HCWs who had never been tested for the coronavirus were less likely to take the vaccines than were the participants who had ever been tested. A study by Laura et al (2023) reported that 96% of participants consumed a COVID-19 vaccine at least once, mostly after infection with the coronavirus (37). This difference in uptake could be due to differences in risk perceptions among HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…We found that HCWs who had never been tested for the coronavirus were less likely to take the vaccines than were the participants who had ever been tested. A study by Laura et al [ 34 ] reported that 96% of participants consumed a COVID-19 vaccine at least once, mostly after infection with the coronavirus [ 42 ]. This difference in uptake could be due to differences in risk perceptions among HCWs.…”
Section: Discussionmentioning
confidence: 99%